Assessment of Stressors and Coping Sources of Inmates in Class II A Corrective Institutions - Anastasia Maratning; Olivia Kristianti; Theresia Jamini; Maria Frani Ayu Andari Dias (Indonesian Journal of Global Health Research, 2024)
Inmates at Class IIA Penitentiary in Banjarmasin face various stressors, including loss of freedom, family isolation, and adaptation to the structured prison environment, which may trigger anxiety and depression. The purpose of this study is to assess stressors and coping sources of inmates in Class II A Corrective Institutions in Banjarmasin City. This study uses a cross-sectional design approach on 75 selected respondents. The sampling technique was purposive sampling. Data were collected through validated questionnaires addressing cognitive, affective, physiological, behavioral, and social aspects and personal, social, material, and spiritual coping resources. Validity was tested using product moment correlation, with coefficient results >0.361, indicating that the instrument is valid. Reliability testing using Cronbach's Alpha produced a value of 0.807 for the stressor questionnaire and 0.703 for the coping source questionnaire, so it was declared reliable. Data analysis was carried out descriptively to describe the frequency distribution and percentage of research variables with the results revealed that 56% of inmates negatively evaluated their stressors, with common symptoms including sleep disturbances (56%) and appetite loss (40%), coupled with low social interaction. Only 8% demonstrated effective coping resources, primarily through prayer, while participation in social activities was minimal. This study shows that inmates at Class IIA Penitentiary in Banjarmasin City The majority of respondents have a negative assessment of the stressors they experience, which reflects an inability to manage stress adaptively. In addition, the coping resources used by most respondents are classified as poor, with reliance on ineffective coping mechanisms and low participation in social and productive activities.